THE FATWA OF THE COUNCIL OF INDONESIAN ULAMA ON INTER-RELIGIOUS MARRIAGE - Lukman Yasin, R. Cecep (De Jure: Jurnal Hukum dan Syari'ah, 2009)
The Qurâ€™anic text states that it is lawful to marry women from among the People of the Book, while in the prophetic tradition it is reported that the Prophet himself had a non-Muslim wife. However, the campaign to propagate Christianization which had been tirelessly carried out by well-organized missionary organizations was reported to have successfully christianized segments of the Indonesian population especially in the heathen hinterland and among outer island tribes. Given the circumstances, the Muslim leaders and ulama perceived inter-religious marriage as a hidden Christianization. The increasing incidence of inter-religious marriage raised the concern of the Indonesian Council of Ulama. Responding to this problem, in June 1, 1980 the Council issued a fatwa which explicitly prohibits a Muslim to marry a non-Muslim. Even though the position adopted by the fatwa was quite a radical departure from the prevalent opinion in classical fiqh text, this legal opinion is still within the permissible frame of Islamic legal theory of maslahah (beneficial theory). This legal theory is encapsulated in the Syafiâ€™i schoolâ€™s legal maxim stating that â€œDarâ€™u al-mafÃ¢sid muqaddam â€˜alÃ¢ jalb al-masÃ¢lihâ€ (Preference is given to the prevention of harm than to attainment of benefit)Al-Quran menegaskan kehalalan menikahi wanita Ahl al-Kitab, sementara hadis menyebutkan bahwa Nabi sendiri beristeri seorang non-Muslim. Namun, gerakan kristenisasi yang dijalankan oleh lembaga missionaris terorganisir telah berhasil memurtadkan sejumlah penduduk Muslim Indonesia, terutama di daerah pinggiran dan pedalaman. Karena itu, para ulama dan pemimpin Islam memandang pernikahan beda agama sebagai bagian dari gerakan kristenisasi terselubung. Tingginya kasus pernikahan beda agama memunculkan keprihatinan Majlis Ulama Indonesia (MUI). Menanggapi masalah ini, pada 1 Juni 1980, MUI mengeluarkan fatwa yang secara tegas melarang seorang pria Muslim menikahi wanita non-Muslim. Meskipun menyimpang dari pendapat yang dianut dalam fiqh klasik, fatwa ini masih berada dalam bingkai teori hukum Islam yang dikenal dengan konsep maslahah. Teori hukum ini dirumuskan dalam kaidah fiqhiyah madzhab Syafiâ€™i yang berbunyi â€œupaya mencegah kemudaratan lebih didahulukan dari pada upaya meraih kemaslahatan.â€Keywords: Fatwa, The Council of Indonesian Ulama, Inter-Religious Marriage